Biochemical and functional characterization of AcUFGT3a, a galactosyltransferase involved in anthocyanin biosynthesis in the red‐fleshed kiwifruit (Actinidia chinensis). Issue 4 (5th December 2017) - Liu, Yanfei; Zhou, Bin; Qi, Yingwei; Liu, Cuihua; Liu, Zhande; Ren, Xiaolin
Abstract : Much of the diversity of anthocyanin pigmentation in plant tissues is due to the action of glycosyltransferases, which attach sugar moieties to the anthocyanin aglycone. This step can increase both their solubility and stability. We investigated the pigmentation of the outer and inner pericarps of developing fruits of the red‐fleshed kiwifruit Actinidia chinensis cv. 'Hongyang'. The results show that the red color of the inner pericarp is due to anthocyanin. Based on expression analyses of structural genes, AcUFGT was shown to be the key gene involved in the anthocyanin biosynthetic pathway. Expression of AcUFGT in developing fruit paralleled changes in anthocyanin concentration. Thirteen putative UFGT genes, including different transcripts, were identified in the genome of 'Hongyang'. Among these, only the expression of AcUFGT3a was found to be highly consistent with anthocyanin accumulation. Fruit infiltrated with virus‐induced gene silencing showed delayed red colorations, lower anthocyanin contents and lower expressions of AcUFGT3a . At the same time, transient overexpression of AcUFGT3a in both Actinidia arguta and green apple fruit resulted in higher anthocyanin contents and deeper red coloration. In vitro biochemical assays revealed that recombinant AcUFGT3a recognized only anthocyanidins as substrate but not flavonols. Also, UDP‐galactose was used preferentially as the sugar donor. These results indicate AcUFGT3a is the key enzyme regulating anthocyanin accumulation in red‐fleshed kiwifruit.